Uncertainty affects cancer-related fatigue among breast cancer women undergoing peripherally inserted central catheter chemotherapy: the chain mediating role of psychological resilience and self-care - Yue Yang; Shihui Liu (BMC, 2024)
Abstract Background Breast cancer patients undergoing chemotherapy via peripherally inserted central catheter often experience serious behavioral and psychological challenges, with uncertainty and cancer-related fatigue being prevalent issues that profoundly impact prognosis. Therefore, this study aimed to investigate the relationship between uncertainty and cancer-related fatigue by employing a chain mediation model to examine the potential mediating roles of psychological resilience and self-care. Methods A cross-sectional study was conducted with 223 breast cancer patients receiving peripherally inserted central catheter chemotherapy at two tertiary affiliated hospitals of China Medical University in Liaoning, China, from February 2021 to December 2022. Participants completed self-reported questionnaires to assess uncertainty, psychological resilience, self-care, and cancer-related fatigue. The collected data were subsequently analyzed using Pearson's correlation analysis, hierarchical regression analysis, and mediation analysis. Results Uncertainty exhibited a significant positive correlation with cancer-related fatigue (p < 0.01) and a negative correlation with psychological resilience (p < 0.01) and self-care (p < 0.01). Uncertainty was found to impact cancer-related fatigue through three pathways: psychological resilience mediated the relationship between uncertainty and cancer-related fatigue (mediating effect = 0.240, 95% confidence interval: 0.188 to 0.298, effect ratio = 53.22%); self-care also mediated this relationship (mediating effect = 0.080, 95% confidence interval: 0.044 to 0.121, effect ratio = 17.74%); furthermore, there was a significant joint mediating effect of psychological resilience and self-care on the association between uncertainty and cancer-related fatigue (mediating effect = 0.042, 95% confidence interval: 0.021 to 0.068, effect ratio o = 9.31%). Conclusion The findings of this study revealed that uncertainty not only directly influenced cancer-related fatigue, but also operated through the mediating effect of psychological resilience, self-care, and sequential mediation of psychological resilience and self-care. Interventions tailored for breast cancer patients receiving peripherally inserted central catheter chemotherapy should target these factors to help alleviate uncertainty, enhance psychological resilience, and improve self-care practices, thereby ameliorating cancer-related fatigue.